2013
DOI: 10.1177/0047287513478501
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Event Impacts, and Mega-Event Support among South African Residents before and after the 2010 FIFA World Cup

Abstract: The purpose of the study was to explore the role of mega-event impacts on perceived satisfaction with quality of life and support among South African residents before and after the 2010 FIFA World Cup. Limited research has empirically tested whether quality of life (QOL) is perceived as an exchange benefit that facilitates resident support of mega-events. Intercept data were collected from residents in five host cities three months before (March 2010) and eight months after (March 2011) the event (N = 3,789). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
196
5
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(226 citation statements)
references
References 78 publications
(117 reference statements)
14
196
5
11
Order By: Relevance
“…Positive effects of hosting such events are also detectable at the individual level. Two studies have shown that South Africans perceived the FIFA 2010 World Cup to have increased community spirit, pride and wellbeing (Gibson et al 2014;Kaplanidou et al 2013). Similar results were found in Sydney after the 2000 Olympic Games (Waitt 2003).…”
Section: Hosting Major Sporting Events and Well-beingmentioning
confidence: 76%
“…Positive effects of hosting such events are also detectable at the individual level. Two studies have shown that South Africans perceived the FIFA 2010 World Cup to have increased community spirit, pride and wellbeing (Gibson et al 2014;Kaplanidou et al 2013). Similar results were found in Sydney after the 2000 Olympic Games (Waitt 2003).…”
Section: Hosting Major Sporting Events and Well-beingmentioning
confidence: 76%
“…Andereck et al, (2005) also found that quality of life creates motivation to residents to support tourism program. Kaplanidou (2013) found quality of life as a significant mediating variable between tourism impacts and increased residents' support on tourism program. Similarly, Neal et al, (2007) and Nunkoo and Ramkissoon (2010) also confirmed the quality of life influences to sustainability in tourism development and residents' support for tourism development.…”
Section: Quality Of Life and Support Tourism Competitive Strategiesmentioning
confidence: 91%
“…Measure for quality of life includes satisfaction with local government services, satisfaction with local business services and non-profit services, satisfaction with community conditions, and satisfaction with other specific issues (Yu, 2011). In tourism research, single and multi-item questions have been developed to measure quality of life as an attitude toward tourism development (Kaplanidou et al, 2013).…”
Section: Theoretical Reviews Quality Of Lifementioning
confidence: 99%
“…First, hard legacy (also known as tangible legacy, such as visitor impacts, buildings, new organizations and projects) and soft legacy (or intangible legacy, such as image enhancement, increased confidence, personal skills and the acquisition of new ideas) are fundamental to existing discussions (e.g., [3,9,15]). The hard or tangible legacy is easily measured and, therefore, attracts more attention.…”
Section: Event Legacy and Ecocmentioning
confidence: 99%